2012
DOI: 10.3310/hta16340
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effectiveness and cost-effectiveness of technologies used to visualise the seizure focus in people with refractory epilepsy being considered for surgery: a systematic review and decision-analytical model.

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 46 publications
(189 reference statements)
0
40
0
Order By: Relevance
“…Recently published critical reviews emphasized the difficulties in the interpretation of diagnostic accuracy studies on presurgical workup for epilepsy surgery, and it was suggested to supplement the currently available imperfect reference standard (consensus decision from a combination of tests) with the outcome following surgery (Burch et al., ,b). The likelihood ratios calculated from these tables reflect the clinical usefulness of the index test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently published critical reviews emphasized the difficulties in the interpretation of diagnostic accuracy studies on presurgical workup for epilepsy surgery, and it was suggested to supplement the currently available imperfect reference standard (consensus decision from a combination of tests) with the outcome following surgery (Burch et al., ,b). The likelihood ratios calculated from these tables reflect the clinical usefulness of the index test.…”
Section: Discussionmentioning
confidence: 99%
“…For determining the diagnostic accuracy of ictal source localization, the reference standard for localizing the seizure‐onset zone was the consensus conclusion of the local multidisciplinary epilepsy surgery team (Rosenow & Lüders, ; Burch et al., ,b). The team included experienced, board‐certified clinical neurophysiologists, epileptologists, and neuropsychologists who evaluated the video‐EEG recordings, able to change between different montages, and who had access to all clinical and neuroimaging data interpreted by an experienced neuroradiologist.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with refractory epilepsy, current treatments include surgical resection of areas affecting epilepsy [139142] and the ketogenic diet or other alternative diets used since the 1970s [143–146]. However, the refractoriness of epilepsy continues to be an unresolved problem.…”
Section: Therapeutic Relevancementioning
confidence: 99%
“…2 For most individuals affected by epilepsy, seizures can be brought under control by drug therapy; however, up to 20-30% of patients do not respond to medication and surgical resection of the epileptic focus may be considered. 3 The initial stage of the workup for surgery usually involves a series of tests to isolate the brain region responsible for the occurrence of seizures. Standard assessment consists of history and physical examination, prolonged scalp video-electroencephalogram (EEG) in an epilepsy monitoring unit, magnetic resonance imaging (MRI) of the brain, and neuropsychological testing.…”
Section: Introductionmentioning
confidence: 99%